Effect of intrauterine infusion of gentamicin in repeat breeding cattle - KUTTY, C IBRAHEEM (The Indian Journal of Animal Reproduction, 2023)
Effect of intrauterine infusion of gentamicin was studied in 40 repeat breeding crossbred cows at Livestock research station, Thiruvazhamkunnu, Kerala. The animals were divided into 5 groups with 12 and IO animals respectively in Gr. I & IV and 6 animals each in other three groups. Group I and II consisted of animals with apparently normal reproductive tract, while groups 111 to V were animals with minor abnormalities of reproductive function. Animals of Group I & III were infused with 80 mg of Gentamicin intrauterine 24 hours after insemination . Gr. IV was treated with 160 - 200 mg of Gentamicin intrauterine during heat followed by Al in the subsequent heat. Gr. II and V were kept as controls. All the animals returning to heat were inseminated once again without any treatment. Success rate of Al among the groups were compared based on pregnancy verification after 60 days of insemination. Out of Gr. I animals, 5 (42 %) conceived by Al followed by post Al infusion and another 3 conceived by I more AI in the subsequent cycle making total conception 8 out of 12 (67 %). In Gr. II (control-I) only I (17 %) animal conceived even after 2 Al each in all the animals. Out of 6 animals in Gr. 111, one animal each conceived by first and second AI making total conception 2 (33 %). In Gr. IV, out of IO animals 4 and 2 animals conceived by the first and second Al following Gentamicin infusion making total conception to 6 (60 %) while in Gr. V (Control -2), no animal conceived even after 2 Al. It is concluded that in repeat breeding animals with apparently normal reproductive tract, post AI infusion of 80 mg Gentamicin gives promising results while in animals suspected for endometritis, 160-200 mg gentamicin infusion during heat followed by AI in the subsequent heat is effective.